Advanced parameter tuning scheme for double CFO based fractional order composite controller synthesis method - Siyi Chen; Yang Shu; Haiyang Kuang; Dongqi Cheng; Ying Luo (Systems Science & Control Engineering)
To improve the tracking and anti-interference performances of permanent magnet synchronous servo systems, it is equally important to design the structure and parameters of the control system. In this study, we propose a novel fractional-order composite control synthesis scheme that incorporates a compensation function observer (CFO) into both the inner and outer loops of the system. Given the complexity associated with simultaneously determining the parameters of both the controller and observer, while also considering dynamic performance indices and nonlinear terms in the system, a two-stage parameter tuning method is systematically developed. This method sequentially employs D-decomposition and optimization algorithms to address these challenges. Finally, by comparing it with various algorithms. The simulation and experimental results show that the proposed method can not only achieve satisfactory tracking performance, but also minimizes the impacts of internal and external uncertainties.